2002
DOI: 10.1074/jbc.m201534200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Human Prokallikrein 6 Reveals a Novel Activation Mechanism for the Kallikrein Family

Abstract: Zyme/protease M/neurosin/human kallikrein 6 (hK6) is a member of the human kallikrein family of trypsinlike serine proteinases and was originally identified as being down-regulated in metastatic breast and ovarian tumors when compared with corresponding primary tumors. Recent evidence suggests that hK6 may serve as a circulating tumor marker in ovarian cancers. In addition, it was described in the brain of Parkinson's disease and Alzheimer's disease patients, where it is implicated in amyloid precursor protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 68 publications
4
57
0
6
Order By: Relevance
“…Indeed, recombinant hK7 and the mouse ortholog of hK8 (mK8) were previously shown to be activated by Lys-C (Hansson et al, 1994;Shimizu et al, 1998). Furthermore, crystallographic studies of the kallikreins hK1, hK6 and mK8 revealed very similar structures (Kishi et al, 1999;Bernett et al, 2002;Gomis-Ruth et al, 2002;Laxmikanthan et al, 2005). From sequence analysis of other kallikreins, it is believed that all of them share a very close ternary structure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recombinant hK7 and the mouse ortholog of hK8 (mK8) were previously shown to be activated by Lys-C (Hansson et al, 1994;Shimizu et al, 1998). Furthermore, crystallographic studies of the kallikreins hK1, hK6 and mK8 revealed very similar structures (Kishi et al, 1999;Bernett et al, 2002;Gomis-Ruth et al, 2002;Laxmikanthan et al, 2005). From sequence analysis of other kallikreins, it is believed that all of them share a very close ternary structure.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the proteolytic activity of this enzyme is indicated by its secretion as a proform, requiring activation, as well as by interaction with inhibitors. It has been demonstrated that hK6 has autocatalytic activity and that it can activate and inactivate itself by cleavage of the propeptide and by internal cleavage, respectively (26,27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunoreactive bands in lanes 2 and 3 of Fig. 1A likely represent fragmented hK6, which is known to have autoactivation and autocatalytic activity (26,27 ).…”
Section: Hk6 Hybrid Assaysmentioning
confidence: 99%
“…Briefly, the N terminus pro-peptide region of KLK1-15, comprising the entire set of pro-peptide ''P'' positions and continuing through the P69 position of the corresponding KLK mature N terminus, in each case, was inserted into the Histagged N terminus of a mutant form of human fibroblast growth factor-1 (FGF*). The FGF* protein is highly soluble (thereby ensuring solubility of the pro-KLK peptide); readily expressed using an E. coli host; contains an unstructured, highly solventexposed N terminus (as with the KLKs) (Blaber et al 1996;Gomis-Ruth et al 2002); is engineered to be resistant to internal proteolysis; and has a mass appropriate for rapid SDS-PAGE quantitation of the hydrolytically released KLK pro-peptide.…”
Section: Production Of Pro-klk Fusion Proteinsmentioning
confidence: 99%
“…Briefly, pro-KLK6 was expressed with the inclusion of a C-terminal Strep-tag and His-tag, respectively. X-ray structure data shows that the KLK6 C terminus is essentially antipodal to the N terminus, and as such, short C-terminal tags do not interfere with the N-terminal pro-region (Bernett et al 2002;Gomis-Ruth et al 2002). The cDNA encoding human prepro-KLK6 was cloned into the pSecTag2/HygroB expression vector (Invitrogen).…”
Section: Production Of Pro-klk Proteinsmentioning
confidence: 99%